Theoretical Inspecting of 211At Radionuclide via Coupled-Channel Model for Fusion Reaction of Stable Nuclei - Z. M. Cinan; T. Başkan; B. Erol; A. H. Yılmaz (Atom Indonesia, 2021)
This work has been carried out to obtain and inspect of 211At radionuclide through fusion reaction. Cross-sections for fusion reaction have been calculated with different interaction combinations and excitations for 19F + 192Os and 18O + 193Ir  reactions. All calculations have been performed on NRV Knowledge Base, CCFULL code, and Wong’s Formula. Firstly, we assigned reaction parameter values taking into account the compatibility with the experimental data 19F + 192Os reaction. Afterward, to enrich studies on 211At radionuclide, we proposed 18O + 193Ir reaction which did not have experimental data in the literature with the method and parameter values we determined. We examined the effects of phonon excitations in projectile and target nuclei on fusion cross sections and barrier distributions. With our research, we showed that the coupled channel model and the calculation codes used to explain the fusion cross-section data and barrier distributions well. This research sheds light on the importance of analyzing important medical radionuclides such as 211At by heavy-ion fusion reactions and encourages new researches.